POTENSI BIOETHANOL DARI LIMBAH KULIT ARI KEDELAI LIMBAH PRODUKSI TEMPE - Mochammad Wachid (Jurnal Gamma, 2011)
Mochammad WachidStaf Pengajar Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian PeternakanUniversitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas 246 MalangEmail: mochammadwachid@yahoo.comABSTRACTEthanol is a colorless clear liquid, volatile, has a pungent aroma and a patio painful skin. In theworld of education the ethanol is used as a disinfectant and solvent in various studies, besides thatethanol can also be a source of energy to overcome the energy crisis. In previous studies of soybeanhusk waste tempe production which has been a waste and can be raw material for ethanol fermentationprocess. The purpose of this research is to increase ethanol soybean husk production, by controllingthe temperature and pH of the fermentation process.The research was conducted in the ITP FPP UMM laboratory by controlling the fermentationtemperature at temperatures 30oC, 35oC, 40oC and pH 4.5, 5, 5.5. The parameters measured werethe levels of ethanol, reducing sugar and pH changes during fermentation 12, 24 and 36 hours.The results showed that the treatment temperature is 30oC with pH 4.5 produce ethanol withthe highest levels of 4.071% at the 36. while the production of ethanol using the fastest treatment at40 oC ph5, 5 at the 12 with 2.748% ethanol levels but decreased thereafter.Keywords: ethanol, soy bran, temperature, pH, fermentation.